Stability of drugs of abuse in synthetic oral fluid investigated using a simple "dilute and inject" method of analysis. Issue 8 (20th May 2022) - Gavrilović, Ivana; Musenga, Alessandro; Wolff, Kim; Woffendin, Alison; Smart, Andrew; Gong, Fan; Harding, Duncan; Cowan, David
Abstract: Human oral fluid is well established as a matrix for drug screening, particularly in the workplace. The need to synthesise synthetic oral fluid (SOF) has been recognised in order to overcome human oral fluid's composition variability. We have used SOF spiked with six common drugs of abuse or their primary metabolites: morphine, amfetamine, benzoylecgonine, cocaine, diazepam, and (−)‐Δ 9 ‐tetrahydrocannabinol (THC) in order to assess the suitability of this matrix for quality assurance purposes. For confirmation of a drug screening test, controls and spiked standards are normally required. All our analytes were detected by LC–MS/MS using a quick and easy "dilute and inject" sample preparation approach as opposed to relatively slower solid‐phase extraction. The limit of detection (LOD) was 10 ng/ml for diazepam and THC and 5 ng/ml for morphine, amfetamine, benzoylecgonine and cocaine. Validation results showed good accuracy as well as inter‐ and intra‐assay precision (CV [%] < 5). Our work highlighted the importance of adding Tween® 20 to the SOF and calibrants to reduce losses when handling THC. Furthermore, drug stability was tested at various temperatures (5°C, 20°C and 40°C), for a number of days or after freeze–thaw cycles. Recommendations regarding storage are provided, the spiked SOF being stable at 5°C for up to 1 week without significant drug concentration loss. Abstract : Synthetic oral fluid has been prepared and spiked with common illicit drugs in order to assess this matrix as a suitable reference material for use in drug screening programmes such as drug driving. All analytes were detected by LC–MS/MS, and the analytical method successfully validated. The stability of drugs in the synthetic oral fluid under various temperatures has been investigated, and recommendations regarding storage provided.